THE USE OF WORDWALL ONLINE GAME IN TEACHING VOCABULARY TO STUDENTS AT SMKN 2 PALOPO - Sapna; Madehang; Usman, Nurhayati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Sapna, 2026. This study investigates the effectiveness of the Wordwall online game application in improving English vocabulary mastery among 11th-grade students in class TKJ A at SMKN 2 Palopo. The problem identified is that students generally struggle with vocabulary mastery, which affects their overall English language skills including speaking, writing, and reading. This research employs a pre-experimental design with a one-group pre-test and post-test approach. The population consisted of 19 students in class XI TKJ A at SMKN 2 Palopo, with all students used as the research sample through total sampling technique. The research instrument used was a multiple-choice vocabulary test, and data were analyzed using a paired sample t-test. The results showed a significant increase in mean scores from 50.74 in the pre-test to 74.74 in the post-test. The t-count value (t₀ = 5.871) exceeded the t-table value (tₜ = 2.101) at a significance level of 0.05 with 18 degrees of freedom. Consequently, the alternative hypothesis (H₁) was accepted and the null hypothesis (H₀) was rejected. These findings confirm that the use of Wordwall online games is effective in improving ESP (English for Specific Purposes) vocabulary mastery of students at SMKN 2 Palopo.